Venous Thromboembolism, Corticosteroids and COVID-19: A Systematic Review and Meta-Analysis. (10th February 2021) - Sarfraz, Azza; Sarfraz, Zouina; Razzack, Aminah Abdul; Patel, Gaurav; Sarfraz, Muzna
The novel coronavirus disease 2019 (COVID-19) predisposes patients to venous thromboembolism (VTE) due to risk factors, severe infection, and severe inflammatory responses. The objective is to determine the risk of developing VTE after corticosteroid administration during COVID-19 treatment. Using PRISMA reporting guidelines, a review was conducted from inception until 20 September 2020 with MESH terms including "venous thromboembolism" and "covid-19, " using MEDLINE, Scopus, CINAHL Plus, and WHO Global Database. The inclusion criteria included studies with COVID-19 patients aged 18 years and older with VTE diagnosed by duplex ultrasonography or computed tomography pulmonary angiography (CTPA). Exclusion criteria were studies with non COVID-19 patients and non-VTE patients aged less than 18 years. Quality appraisal was conducted of included studies using the Newcastle-Ottawa Scale (NOS). A random-effect model using 95% confidence intervals, and significance of findings was assessed using Review Manager V5.4.We included 12 observational studies with 2801 patients (VTE n = 434; non-VTE; n = 2367). Patients had a higher risk of presenting with VTE when being administered corticosteroids during treatment of COVID-19 (RR = 1.39, 95% CI = 1.10 to 1.77, I 2 = 0%). A positive effect size was found (SMD = 1.00, 95% CI = 0.67 to 1.32, I 2 = 85%) for D-dimer laboratory values (µg/mL) in the VTE group. While critically ill COVID-19 patients are more likely to require corticosteroid treatment, it may be associated with increased risk of VTE, and poor clinical prognosis. Risk assessment is warranted to further evaluate patients as case-by-case in reducing VTE and worsening clinical outcomes.